2017
DOI: 10.3389/fmicb.2017.02362
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bronchoalveolar Lavage Fluid Cytokines as Biomarkers for Invasive Pulmonary Aspergillosis in At-Risk Patients

Abstract: Background: Invasive pulmonary aspergillosis (IPA) is an infection that primarily affects immunocompromised hosts, including hematological patients and stem-cell transplant recipients. The diagnosis of IPA remains challenging, making desirable the availability of new specific biomarkers. High-throughput methods now allow us to interrogate the immune system for multiple markers of inflammation with enhanced resolution.Methods: To determine whether a signature of alveolar cytokines could be associated with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 49 publications
2
61
0
Order By: Relevance
“…The pro‐inflammatory profile of the Suspected IPA group and the IPA group is in concordance with the study of Gonçalves et al that examined a heterogeneous group of immunocompromised patients including solid organ transplants with IPA. They found significantly higher levels of IL‐1b, IL‐6, IL‐8, IL‐17A, IL‐23, and TNF‐alpha in BAL compared to controls without IPA . Differences in the specific cytokines pro‐inflammatory between our cohort and theirs can be explained by the fact that our samples were collected at the time of Aspergillus isolation when the patients did not meet criteria for probable or proven IPA.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The pro‐inflammatory profile of the Suspected IPA group and the IPA group is in concordance with the study of Gonçalves et al that examined a heterogeneous group of immunocompromised patients including solid organ transplants with IPA. They found significantly higher levels of IL‐1b, IL‐6, IL‐8, IL‐17A, IL‐23, and TNF‐alpha in BAL compared to controls without IPA . Differences in the specific cytokines pro‐inflammatory between our cohort and theirs can be explained by the fact that our samples were collected at the time of Aspergillus isolation when the patients did not meet criteria for probable or proven IPA.…”
Section: Discussionmentioning
confidence: 74%
“…Cytokine profiles have been classically studied in serum rather than BAL samples, and there is a lack of studies of cytokines in BAL 29 Differences in the specific cytokines pro-inflammatory between our cohort and theirs can be explained by the fact that our samples were collected at the time of Aspergillus isolation when the patients did not meet criteria for probable or proven IPA.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also found increased production of IL-6 by A549 pulmonary epithelial cells and primary epithelial cells [37], and this is thought to play an important role in T-cell recruitment. Other studies have shown that in vitro opsonization of A. fumigatus conidia with H-ficolin, L-ficolin [38], and M-ficolin play essential roles in pathogen recognition and complement activation through the lectin pathway and potentiate IL-8 secretion by A549 lung epithelial cells [39,40].…”
Section: Anti-mold Immune Response: the Impact Of The Host And The Pamentioning
confidence: 99%
“…The alveolar concentrations of PTX3 are known be determined at the genetic level (Cunha et al 2014), and, as such, one could expect a further improvement to the diagnostic performance of PTX3 by knowing in advance the genotypic profile of the patient. In addition, PTX3 deficiency was also shown to influence the levels of alveolar cytokines in hematological patients suffering from IPA and to impact their ability in discriminating infection (Gonçalves et al 2017). More important, reinstating the normal levels of PTX3 in vitro with the recombinant protein was sufficient to restore the efficacy of the antifungal effector functions of neutrophils (Cunha et al 2014).…”
Section: Soluble Pattern Recognition Receptorsmentioning
confidence: 99%